LOGICAL-ALGORITHMIC PROCESSING OF TEXT INFORMATION IN THE ELECTRONIC GOVERNMENT SYSTEM - KhasanovichNishanov, Akhram; SherzodNorboyo'g'li, Saidrasulov; ElmuradSatimbaevich, Babadjanov (The journal of contemporary issues in business and government, 2022)
The article examines the issue of automatic processing of text appeals of individuals and legal entities in the e-government system, proposing a logical mathematical and algorithmic support for the effective use of natural language to provide information services in public administration reform. The study proposes a model of processing text documents, which allows to classify the texts of written appeals of individuals and legal entities in automated systems of government agencies. The algorithm for solving the problem of determining the purpose of natural and legal appeals of individuals and legal entities, as well as the necessary bases for the automatic identification of the organization serving written appeals were expressed mathematically and the mathematical solution of turning appeals into needs and its search was studied.